Determinants and structural development of FDI in Pacific-Rim developing countries - Jamuna Prasad Agarwal (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
The movements of foreign direct investment (FDI) in the recent past are marked by a relatively very high growth in the Pacific Rim (PR) countries (Australia, Brunei, China, Hongkong, Japan, Indonesia, Malaysia, Papua New Guinea, New Zealand, Philippines, Singapore, Taiwan, Thailand). The developing countries of this area were able to raise considerably their share of the total world outflows in the first half of this decade (Table Al) . In the following analysis an attempt is made to work out the determinants of FDI in these countries. Unlike trade there is no well developed general theory explaining all patterns of FDI. Therefore a useful approach is to look at the past record of these countries in the light of factors such as economic growth, level of development or political relations, which generally play an important role in the inflow of these investments.
Keywords: 330; Direktinvestition; Pazifischer Raum